Ethyl 2-(Diisopropoxyphosphoryl)-2H-azirine-3-carboxylate: reactions with Nucleophilic 1,3-Dienes - Lemos, A. (2009)
Ethyl 2-(diisopropoxyphosphoryl)-2H-azirine-3-carboxylate, the first example of an azirine bearing simultaneously ester and phosphonate groups was generated in situ and reacted with a number of 1,3-dienes. Cycloadducts or their ensuing rearranged products were isolated in moderate yields.